EIB Working Papers 2019/11 - Macro-based asset allocation An empirical analysis (Volume 2019/11) - Schmieder, Christian (European Investment Bank, 2020)
Macro-based asset allocation is based on the identification of turning points in macro-financial cycles. This paper suggests that macro-based asset allocation informed by trends in continuous business and financial cycle indicators could be a promising alternative for medium- and long-term investment strategies. Despite changes during the last three decades, the most promising specifications of this approach did roughly anticipate turning points in asset price cycles, implying favourable returns and low portfolio volatility.